A low-frequency anechoic coating under high hydrostatic pressure by pressure balancing strategy - Ningdong Hu; Jun Jin; Hongping Hu (Journal of Low Frequency Noise, Vibration and Active Control)
It has always been a challenge to develop low-frequency anechoic coatings under high hydrostatic pressure. Based on active pressure balancing strategy (APBS), the airbag embedding in Helmholtz resonator model is proposed to achieve low-frequency and broadband sound absorption under high hydrostatic pressure. Compared with some existing pressure resistance schemes, the proposed anechoic coating has a thinner and lighter structure, lower sound absorption frequency band, and can withstand higher pressure. The proposed anechoic coating achieves sound absorption coefficient larger than 0.5 within the bandwidth of 24.5∼1000 Hz under pressure of 0.1 MPa, and within the bandwidth of 73.6∼1000 Hz under pressure of 5 MPa. The thickness of 10 mm is less than 1‰ of the incident wavelength at 100 Hz. The proposed model provides a new solution to the problem of improving low-frequency sound absorption performance of the anechoic coating under high hydrostatic pressure.